Production Of Nano-Carbon Using Arc Discharge In Liquid Nitrogen - Sulaiman, Yusran; Buang, Nor Aziah; Sanip, Suhaila; Ismail, Ahmad Fauzi (2004)
Arc discharge is a well-known method for the production of carbon nanotubes (CNTs). From the arc discharge method. various kinds of CNTs such as single-walled carbon nanotubes (SWNTs), multi-walled carbon nanotubes (MWNTs) and carbon onion can be produced. Other than these structures, single-walled nanohoms (SWNHs) and their metal-including form can also be synthesized by modifying the system i.e. replacing the vacuum system with liquid nitrogen (LN). They are considered as a novel nanocarbon structure. This mcthod can bc an economical route for the mass production of CNTs.